(untitled) (Communications in Computational Chemistry, 2025)
In this work, we perform all-atom and coarse-grained dynamics simulations to predict the mechanical properties of a typical synthetic protein system. Previous experiments showed that proteins with a larger molecular weight exhibit better mechanical performance. Our steered molecular dynamics (SMD) simulations at the all-atom level only capture intermolecular interactions and fail to reproduce this tendency. The results of the dissipative particle dynamics (DPD) simulations at the coarse-grained level are consistent with experiments. The comparison between two levels of resolution highlights the importance of simulation scales in predicting mechanical properties of complex systems. We also reveal some underlying factors correlated with the mechanical properties of synthetic proteins, such as molecular weights, fabrication processes, the ratio of hydrophobic to hydrophilic segments and their order in the amino acid sequences.